2017
DOI: 10.1016/j.drugalcdep.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparing adult cannabis treatment-seekers enrolled in a clinical trial with national samples of cannabis users in the United States

Abstract: Background Cannabis use rates are increasing among adults in the United States (US) while the perception of harm is declining. This may result in an increased prevalence of cannabis use disorder and the need for more clinical trials to evaluate efficacious treatment strategies. Clinical trials are the gold standard for evaluating treatment, yet study samples are rarely representative of the target population. This finding has not yet been established for cannabis treatment trials. This study compared demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…However, the observed rate in the current study more closely approximates the observed rate in a prior multisite clinical trial for CUD (38%; McClure et al, 2018). It may be the case that those who participate in research studies, even via online recruitment sources, are different from those in the general population (i.e., those who complete household surveys; McClure et al, 2017;Susukida, Crum, Stuart, Ebnesajjad, & Mojtabai, 2016), which may have impacted prevalence rates and the characteristics of the current sample of co-users. Finally, all data in this study were self-reported, which does not allow for the biochemical confirmation of cannabis and tobacco co-use.…”
Section: Limitationssupporting
confidence: 67%
“…However, the observed rate in the current study more closely approximates the observed rate in a prior multisite clinical trial for CUD (38%; McClure et al, 2018). It may be the case that those who participate in research studies, even via online recruitment sources, are different from those in the general population (i.e., those who complete household surveys; McClure et al, 2017;Susukida, Crum, Stuart, Ebnesajjad, & Mojtabai, 2016), which may have impacted prevalence rates and the characteristics of the current sample of co-users. Finally, all data in this study were self-reported, which does not allow for the biochemical confirmation of cannabis and tobacco co-use.…”
Section: Limitationssupporting
confidence: 67%
“…Finally, given that co-occurring psychiatric disorders were exclusionary in this trial, this study sample may not have been truly representative of the general population of those meeting for a cannabis use disorder. Indeed, in a comparison of the current study sample with national datasets, there was greater representation of non-tobacco users within the current study sample (McClure et al, 2017). Those with cannabis use disorder and other co-occurring disorders may have complex presentations and future studies should work to improve sample representativeness.…”
Section: Discussionmentioning
confidence: 89%
“…Many trials struggle or fail to meet their target sample size 1 and/or have largely unrepresentative samples. 2 Trials that target lower prevalence behaviors (eg, tobacco use comorbid with a physical or mental health disorder) face even greater challenges, to the point where locally conducted trials may be infeasible. Multisite clinical trials can overcome some of these hurdles but incur their own unique challenges, including the need for sizable and costly infrastructure, site training and monitoring, regulatory hurdles, and centralized versus local data management.…”
Section: Introductionmentioning
confidence: 99%